Making Social Protection Information Systems Adaptive - World Bank (World Bank, Washington, DC, 2020)
The Information Systems used by Social Protection (SP) programs are an invaluable resource for monitoring, managing, and delivering SP benefits and services to poor and vulnerable populations. These are often the public information systems that contain more detailed information on persons that interact with public agencies. At the same time, pervasive disaster risk in Latin America and the Caribbean (LAC) warrant improved use of data and information to build the resilience of those most vulnerable, and for making quick decisions in post-disaster contexts, often in data-constrained environments. Given this, there is increased recognition of the utility of SP Information Systems (SPISs) to help address Disaster Risk Management (DRM) objectives. Some countries in LAC have been pioneers in piloting, using and integrating SPISs to improve delivery and coordination for regular SP benefits and services. On the other hand, there remains several countries in the region, who are still using rudimentary systems for data and information management of their SP programs and services. There is also little evidence from the region of effective data sharing and interoperability across SP and DRM information systems, compounded by weak data policies and standards in some countries. Given this, there remains significant untapped potential for more effective use of SPISs to address disaster and climate-related risks in the region. This guidance note summarizes how LAC countries can better use their SPISs to support Adaptive Social Protection (ASP) and DRM objectives. While the note has a focus on disasters caused by natural hazards, the framework and lessons are also applicable to other types of emergencies and shocks.